Status of birth preparedness and complication readiness among recently delivered women: a community based study in a slum of Kolkata, West Bengal - Ghosh, Ayon; Dasgupta, Aparajita; Paul, Bobby; Bandyopadhyay, Lina; Sembiah, Sembagamuthu; Mallik, Nazrul (International Journal Of Community Medicine And Public Health, 2017)
Background: Birth preparedness and complication readiness (BPACR) is a strategy that promotes timely use of skilled care and deal with emergencies especially during childbirth, by encouraging pregnant mothers and their families to make effective plan for child birth. The objective of the study was to assess the awareness and practices of BPACR among women who had delivered in last 24 month and identify the predictors of favourable BPACR. Methods: A cross sectional, community based study was conducted in a slum of Chetla, Kolkata, among 98 women who delivered during the previous 2 years. Data were collected with a structured, interview schedule after obtaining informed consent from them. Results: Out of 98 women only 43 (43.9%) were well prepared for birth and its complication in their last pregnancy. 32.7% women were knowledgeable about danger sign of pregnancy. 100% of study participants identified the place of delivery and made a birth plan with discuss with family members. Bivariate logistic regression shows education status of study subject OR (CI) 4.34 (1.4712.8), education status of their spouse OR (CI) 2.92 (1.187.24) and per capita income OR (CI) 7.18 (2.6619.34) have significant association with birth preparedness. However in multivariable logistic regression after adjustment with different confounding variable only income remained significant AOR (CI) 5.82 (2.0816.29). Conclusions: The poor status of BPACR as observed in this study calls for increased emphasis on counselling of pregnant women and their families regarding the different components of birth preparedness.